(x – 1) + 2x (x – 4)
không có j ở đây đâu
----- Nội dung dịch tự động từ ảnh -----
a)(x – 1) + 2x (x – 4)
= x? – 2x +1+ 2x? – 8x
= 3x? – 10x +1
– (x – 1)?
b) (x – 3) (x+ 3)
= x? – 9 – x2 + 2x – 1
|
= 2x – 10
c)(x + 5) – x (4x – 7)
= x? + 10x + 25 – 4x? + 7x
= -3x? + 17 + 25
d) (x – 2) (x + 2) – (3x – 1)?
= x? – 4 – 9r² + 6x – 1
-
= -8x? + 6x – 5
e) (8x – 1) (x – 4) + (x – 2)²
= 8x? –
32x – x +4 +x² – 4x +4
= 9x? .
37x +8
f)(x + 2)° – 2x (2² + 12)
= x³ + 6x? + 12x +8 – 2x3 – 24x
2³ + 6x²
= -a³ + 6a?
9)(4x – y) – (2x - y) (x + 5y)
16x? – 8xy +y² – 2x² – 10xy + xy+5y²
14x? – 17ry + 5y?
12x + 8
|
-
k)(2x – 1) – (x – 3) (x +3)
= 4x? –
4x +1- x2 + 9
= 3x? – 4x + 10